IMPROVING INFORMATION LITERACY THROUGH GAMIFICATION: FANTASY BRAND LEAGUES. Issue 2 (3rd April 2019) - Ashley, Christy
Abstract : Undergraduate marketing majors who were enrolled in the senior-level marketing capstone course engaged with current marketing news from credible sources and practiced data visualization as part of a teaching innovation, Fantasy Brand Leagues. The ten-week assignment treated brands like players in a game modeled after Fantasy Football. The assignment improved preparation for class discussion and created a competitive atmosphere where students were more motivated to engage with the content and in-class discussions about current events related to marketing. It improved student confidence in marketing knowledge and data visualization skills and, perhaps most importantly, prepared students for self-directed learning.